Implementation of correlative enhanced scattering diagnostics of small scale plasma turbulence at the FT-2 tokamak - Budnikov, V.N.; Gurchenko, A.D.; Gusakov, E.Z.; Esipov, L.A.; Kantor, M.Yu.; Kouprienko, D.V.; Lashkul, S.I.; Novik, K.M.; Selenin, V.L.; Stepanov, A.Yu.; Vekshina, E.O. (Вопросы атомной науки и техники, 2002)
In this paper the first results of implementation of CES
diagnostics at the FT-2 tokamak possessing much more
developed set of standard tokamak diagnostics are
presented.